ملتان کی تاریخی، تہذیبی و ثقافتی عکاسی: سرائیکی ناول "بیڑی وچ دریا'' (Al-Qamar, 2024)
Saraiki Novel''بیڑی وچ دریا''(River in a Boat) which has come out to highlight the history, Civilization and Culture of Multan. This Novel is authored by Dr. Aslam Ansari, it is a journey of both body and Soul. The title of the novel also indicates that the tree is a metaphor for the heart and the river is the emotions, feelings and thoughts, contained in it. Characterization, Scenes, Dialogues, Emotions and details in the novel are of high quality. The author's grip on the plot seems very strong. His artistic and intellectual qualities are Saraiki. Dr. Aslam Ansari's novel "River in a Boat" has made a conscious effort to preserve the centuries-long history of Multan. So, he has to risk his life. Sanwal has to Travel to Delhi and Ajmer to fulfill his promise to rescue Heer Dikhan Vasu from the mire of sin. Sher Khan, a representative of the class, forcibly picks her up and marries her. But the same Sher Khan is killed by his nephews; references to the play are an important part of the novel. Sanwal is deeply saddened when sarang is killed in a battle with the British. There is a time that even after finding love the grief of the death of his friend Sarang due to the British occupation, the pain of injustice forces Sanwal to throws himself in to the river. The plot of the "River in the Boat" is fast and beautifully decorated. The language of the novel is convoluted and confused. The Style is charming and reminiscent of the general tone of ancient Times. The Scenes of urban life are good, while the rural scenes have a sense of thirst. In the first part of the novel, an attempt has been made two draw a map of 150 years old Multan.Sarang's innocence is proved due to Sanwal testimony during the moul Raj brutal treatment of the residents of Multan in 1888 has been made clear. Later, the account of British captured Multan.
Keywords: "River in the Boat"; History; Civilization and Culture of Multan; Highlighted in Dr: Aslam Ansari's Novel